Assessing Patient Safety And Quality Of Care: A Comparative Study Of Hospitals In Tamil Nadu - Preethi R; Dr. P. Marishkumar; Dr. S. Subhasini (Revista Electronica de Veterinaria, 2024)
This study aimed to evaluate and compare patient safety and quality of care across selected hospitals in Tamil Nadu, focusing on Apollo Hospitals (private), Madras Medical College, and Government General Hospital (public). Using a cross-sectional survey design, data were collected from 415 participants including healthcare professionals and administrative staff. The study investigated patient safety incidents, such as medication errors and surgical complications, and quality of care metrics, including patient satisfaction, timeliness of care, and communication. Major findings revealed that Apollo Hospitals reported fewer safety incidents and higher scores in patient satisfaction and communication compared to the public hospitals. Statistical analyses confirmed significant differences in safety incidents and quality metrics across the hospitals, indicating that hospital type influences these outcomes. The study concludes that private hospitals generally outperform public hospitals in safety and quality of care metrics. These findings highlight the need for targeted improvements in public hospitals and suggest that adopting best practices from private institutions could enhance overall healthcare delivery.